Following drug degradation and consequent taste deterioration of an oral reconstituted paediatric suspension during dosing interval via electronic tongue - Abdel Naser Zaid; Rowa Al Ramahi; Alaaldin AlKilany; Nawaf Abu-Khalaf; Maher El Kharouf; Dana Abu Dayeh; Leena Al-omari; Mohammad Yaqoup (Elsevier, 2022)
Background: The taste of oral liquid dosage forms is a crucial factor that impacts pediatric patient compliance. Taste of suspensions can be typically evaluated by human volunteers. Recently, the electronic tongue (ET) has been proven as an emerging tool that could be useful to follow up various formulations' properties like taste and composition. This study aimed to evaluate the potential use of ET in assessing the taste deterioration of reconstituted oral suspensions and compare the results obtained with the typical in vivo panel taste method. Methods: Four commercially available brands of amoxicillin/ clavulanic acid suspensions (one brand and three generic formulations) were reconstituted and stored in refrigerator to assess their taste on a daily basis. The taste of these products was assessed using Alpha-Astree ET and the obtained results were compared with those obtained from an in vivo panel taste assessment using a hedonic panel test (the 5-point hedonic scale). Results: All evaluated suspensions exhibited similar trends. ET and in vivo analysis indicated low taste scores for all evaluated suspensions immediately after reconstitution, possibly due to the incomplete dissolution of sucrose. The scores for all formulations were higher on day 2, followed by a steady state for the next two days. After that, a significant decay in the scores was observed in the fifth day for all evaluated suspensions. ET results were in excellent agreement with the results obtained via in vivo panel test method. Conclusion: The ET seems to be promising for testing the taste of pharmaceutical liquid preparations and evaluate possible deterioration upon storage or after reconstitution. It may provide a platform to avoid the involvement of pediatric volunteers in clinical evaluation and can be employed as a quality control tool during manufacturing.